Organizational Learning in Public Tertiary Educational Institutions - Akanpaadgi, Emmanuel (Archives of Business Research, 2020)
The study sought to examine how public tertiary educational institutions in Ghana can make use of organizational learning in order to improve upon their performance. Although organizational learning has proven to be beneficial to some organizations, it is not being utilized by public tertiary educational institutions in Ghana. The phenomenological research methodology was used to describe the experiences of the researcher in relation to the subject. Secondary data was also reviewed and analysed. The study concluded that for public tertiary educational institutions in Ghana to benefit from organizational learning, they must fully embrace Information Communication Technology while appointing leaders who understand the need to adopt organizational learning as a means of encouraging teamwork.